IMPLEMENTASI KEBIJAKAN PENGELOLAAN SURAT PERINTAH PERJALANAN DINAS BERBASIS WEBSITE (E-SPPD) DI SUB BAGIAN PERJALANAN BIRO UMUM DAN PROTOKOL PROVINSI PAPUA - Jimmy Soter Reyaan; Nur Aedah; Septinus Saa (Universitas Cenderawasih, 2023)
The problem of how to implement the Electronic-based Business Travel Order Management Policy (E- SPPD) in the Travel Division of the General Bureau and Protocol of the Papua Province and what are the supporting and inhibiting factors for the Implementation of the Electronic-Based Business Travel Order Management Policy (E-SPPD) in the Travel Division of the General and Protocol Bureau of the Papua Province were developed as a result of this research. This study aims to explain and assess the Electronic-Based Service Travel Order Management Policy (E-SPPD) implementation process as well as the factors that support and hinder the implementation of the Electronic-Based Business Travel Order Management Policy. A study that describes the Implementation of Website-Based Business Travel Order Management Policy (E-SPPD) in the Travel Subdivision of the General Bureau and Protocol of Papua Province is an example of the descriptive qualitative research type. This kind of phenomenological research aims to paint a clear picture of the issues under investigation based on the informants' personal experiences. Network issues and system flaws, a lack of facilities and infrastructure, a lack of staff, manual disposition and application systems that can only be signed by the definitive Regional Secretary mean that work on the Official Travel Order (SPPD) will be done manually by Plh. Sekda if the Regional Secretary is not in the area. who signed it, despite the fact that its advantages can increase productivity by accelerating the creation of Website/Electronic Based Service Travel Orders (E-SPPD) and Factors the author met during interviews and field research.